Comprehensive approach to the National Network of Teleaudiology in World Hearing Center in Kajetany, Poland - Piotr Henryk Skarżyński; Weronika Świerniak; Łukasz Bruski; Maciej Ludwikowski; Henryk Skarżyński (Finnish Social and Health Informatics Association, 2018)
To improve the quality of patient care, the Institute of Physiology and Pathology of Hearing (IPPH) developed and implemented into the clinical practice in 2009 the National Network of Teleaudiology (NNT). NNT is a specialized network allowing the use of the internet and modern IT tools to provide medical care, rehabilitation and technical support for patients visiting a one of the affiliated policlinics of the Institute. This was the basis for the development and implementation of the implant fitting procedure, using modern internet and telediagnostic technologies - telefiting. This procedure, implemented in several centers throughout the country and aboard, solves the growing need for constant specialist care, check-ups and periodic reviews of speech processors. Clinical engineers, through teleconferencing links, can carry out the whole process of assessing and fitting the cochlear implant assisted by auxiliary staff of the cooperating center. Material of this study consisted of 316 cochlear implant users scheduled for telefitting in one of 8 centers selected for this study. Each patient underwent a teleconsultation procedure. After telefitting the patient was presented with a questionnaire consisting of questions relating to the quality and time effectiveness of telefitting and the preparation process, assessment of the ease of contact with the audiologist, the sense of security and calm during the session, and an overall assessment of its usefulness as an alternative to different kinds of standard visits. Significantly smaller distances that have to be overcome by patients to cooperating centers have significantly reduced the travel time. The benefits of the telefitting program include the results of surveys, the satisfaction of which was reported by majority of them.